Penegakan Hukum HAM dalam Bingkai Hukum Progresif Berdasarkan Kasus Paniai di Papua - Rufaidah Rufaidah; Nanik Prasetyoningsih (Media of Law and Sharia, 2023)
In Indonesia, there is a need for a new legal breakthrough in the enforcement of human rights law. Progressive law can be used as a legal thought in enforcing human rights law. Considering progressive law is a law that does not rely on the text of the law alone but can be sourced from the values of people's lives. This study will discuss the Enforcement of Human Rights Law in a Progressive Legal Perspective. Efforts to enforce human rights law and protect human rights in Indonesia, apart from being regulated through regulations, can also be legally processed through human rights courts. The thing that underlies the urgency of the Progressive legal approach is that the judiciary, which is a justice enforcement agency, has not provided the best results in the justice enforcement process. What needs to be emphasized and underlined is that progressive law is different from other laws which prioritize strict procedures rather than prioritizing the objectives of the law itself. Enforcement of human rights law is often difficult, due to the many requirements and regulations as well as political dynamics that hinder the legal process for enforcing human rights law. Komnas HAM as an institution that has responsibility for the implementation of human rights law enforcement, preferably in the process of resolving human rights law, or seeking human rights justice, does not only build a legal rationale based on the positivistic paradigm.